2018
DOI: 10.1097/sap.0000000000001339
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Residents on Patient Satisfaction

Abstract: Overall, patients expressed high levels of satisfaction with the quality of physician communication with and without resident involvement. Resident physician involvement in surgical clinic visits was associated with lower overall patient satisfaction and decreased likelihood of recommending the practice. In addition, we observed that resident involvement was not associated with lower communication scores in most surgical specialties, including Plastic Surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
3
11
1
Order By: Relevance
“…The overall response rates of Site A (17.5%) and Site B (18.0-25.0%) are comparable to other published studies that have used Press-Ganey Medical Practice Survey [39][40][41][42][43]. R/E-specific response rates were available at Site A (NHW: 22.7%; Latino: 14.3%; African-American: 13.6%; Asian: 11.8%; Multiracial/Other Race: 11.9%; Missing/Unknown: 15.0%).…”
Section: Samplingsupporting
confidence: 83%
“…The overall response rates of Site A (17.5%) and Site B (18.0-25.0%) are comparable to other published studies that have used Press-Ganey Medical Practice Survey [39][40][41][42][43]. R/E-specific response rates were available at Site A (NHW: 22.7%; Latino: 14.3%; African-American: 13.6%; Asian: 11.8%; Multiracial/Other Race: 11.9%; Missing/Unknown: 15.0%).…”
Section: Samplingsupporting
confidence: 83%
“…Otolaryngology was one of three specialties for which resident participation had this association; there were nine surgical specialties included. 23 The subjects in this study reported longer wait times when residents were involved in the visit. This could be because patients perceived time spent with the resident physician as part of their wait time.…”
Section: Discussionmentioning
confidence: 71%
“…This large, cross‐sectional study of Press Ganey surveys showed decreased patient satisfaction when residents were involved in the clinic visit (88.7% vs. 90.4%, P < .001). Otolaryngology was one of three specialties for which resident participation had this association; there were nine surgical specialties included . The subjects in this study reported longer wait times when residents were involved in the visit.…”
Section: Discussionmentioning
confidence: 92%
“…Li et al .’s survey showed that patients’ satisfaction with their physician’s communication did not change when plastic surgery residents were involved in their care, unlike some other surgical specialties. 24 …”
Section: Discussionmentioning
confidence: 99%